The subtle knife - Pullman, Philip, 1946- (New York : Dell Laurel-leaf, 2003)
As the boundaries between worlds begin to dissolve, Lyra and her daemon help Will Parry in his search for his father and for a powerful, magical knife.
Sequel to: The golden compass.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
7.6
5-8
Keywords: Fantasy; Interplanetary voyages -- Fiction; Knives -- Fiction; Interplanetary voyages -- Fiction; Knives -- Fiction; Fantastic fiction